BOSE-EINSTEIN CORRELATIONS IN PION PRODUCTION AT TRISTAN (Journal of Sciences, Islamic Republic of Iran)
Measurement of Bose-Einstein correlations in the production of like-signed pion pairs has been made with the AMY detector at TRISTAN. An event sample of 10120 hadronic events with ranging between 50 to 61 GeV was used. These measurements indicate a strength of the enhancement of ? = 0.61M.07, with a typical correlation size of Ro = 1.16±.08 fm. This value of ? is consistent with measurements at lower energies; however, Ro is somewhat larger than lower energy results have indicated